Efficacy and Safety of Lactobacillus plantarum K50 on Lipids in Koreans With Obesity: A Randomized, Double-Blind Controlled Clinical Trial - Sohn, Minji; Na, Ga Yoon; Chu, Jaeryang; Joung, Hyunchae; Kim, Byung-Kook; Lim, Soo (Frontiers in Endocrinology, 2022)
Background: Only few studies have investigated the role of probiotics in the development of obesity. We aimed to determine the efficacy and safety of an intake of Lactobacillus plantarum K50 (LPK) on body fat and lipid profiles in people with obesity. Methods: This randomized, double-blind, placebo-controlled, clinical trial involved 81 adults with a body mass index of 25–30 kg/m2 who were assigned randomly to a diet including 4 x 10^9 colony forming unit of LPK or a placebo. Changes in body fat, anthropometric parameters, and biomarkers of obesity were compared using a linear mixed-effect model. Results: After 12 weeks of treatment, body weight, fat mass, and abdominal fat area did not change significantly in the two groups. However, total cholesterol levels decreased from 209.4 ± 34.4 mg/dL to 203.5 ± 30.9 mg/dL in the LPK group, but increased from 194.7 ± 37.5 mg/dL to 199.9 ± 30.7 mg/dL in the placebo group (P = 0.037). Similarly, triglyceride levels decreased from 135.4 ± 115.8 mg/dL to 114.5 ± 65.9 mg/dL in the LPK group, with a significant difference between groups. LPK supplementation also tended to decrease leptin levels compared with placebo. It also changed the distribution of gut microbiota significantly, with an increase in L. plantarum and a decrease in Actinobacteria, both of whose changes in abundance were correlated with changes in visceral adiposity, with borderline significance. Conclusion: A 12-week consumption of LPK reduced the total cholesterol and triglyceride levels significantly with favorable alterations in microbiota, suggesting potential benefits for controlling blood lipid profiles.